Immune inactivation by VISTA predicts clinical outcome and therapeutic benefit in muscle-invasive bladder cancer - Wandi Li; Zhaopei Liu; Kaifeng Jin; Fei Shao; Han Zeng; Yiwei Wang; Yu Zhu; Le Xu; Zewei Wang; Yuan Chang; Weijuan Zhang (BMC Cancer, 2023)
Abstract Background V domain Immunoglobulin suppressor of T cell activation (VISTA) has been proved to be a novel immune checkpoint molecule that positively regulates T cell infiltration in several malignancies. However, the clinical impact of VISTA on muscle-invasive bladder cancer (MIBC) patients remains relatively obscure. Methods This study enrolled 135 MIBC patients from Zhongshan Hospital (ZSHS) and 391 patients from The Cancer Genome Atlas (TCGA) to examine the VISTA expression and immune contexture based on immunohistochemistry (IHC) staining and CIBERSORT algorithm. Additionally, IMvigor210 Cohort included 195 bladder-derived urothelial carcinoma patients to evaluate the efficacy of immunotherapy. Kaplan-Meier curve and Cox regression analyses were conducted to assess clinical outcomes. Results MIBC patients with high VISTA+ immune cells (ICs) possessed poor overall survival and inferior therapeutic responsiveness to adjuvant chemotherapy (ACT), but superior responsiveness to PD-L1 inhibitor. VISTA+ ICs infiltration shaped an immunoevasive context featured by regulatory T cells (Tregs), M2 macrophages, mast cells and exhausted CD8+ T cells infiltration, with increased interleukin 10 (IL-10), transforming growth factor-β (TGF-β) and interferon-γ (IFN-γ), but also elevated T-cell immunoglobulin mucin-3 (TIM-3), lymphocyte activation gene 3 (LAG-3) and T-cell immunoglobulin and ITIM domain (TIGIT), which was also mainly presented in basal-squamous and luminal-infiltrated subtypes of MIBC. Conclusion VISTA+ ICs infiltration could be an independent predictor to identify poor prognosis and therapeutic responses (PD-L1 blockade and ACT) in MIBC patients, which was associated with immunoevasive contexture. The novel immune checkpoint VISTA might be utilized as a candidate treatment biomarker in MIBC patients.